The Effects of Antibiotic Growth Promoter, Probiotic or Organic Acid Supplementation on Performance, Intestinal Microflora and Tissue of Broilers - Gunal, M.; Yayli, G.; Kaya, O.; Karahan, N.; Sulak, O. (International Journal of Poultry Science, 2006)
Effects of an antibiotic growth promoter (flavomycin), a probiotic mixture (protexin) or a mixture of organic acids including plant extract and mineral salts (genex) on performance, intestinal microbial flora and tissue morphology have been examined in 160 day-old Ross 308 broiler chicks. Commercial corn-soybean-based broiler starter and grower diets were formulated as basal diets for control treatment. Basal diets were supplemented with a probiotic (0.1% protexin), an antibiotic growth promoter (0.1% flavomycin), an organic acids mixture (0.2% genex) or a combination of a probiotic with an organic acids mixture (0.1% protexin+0.2% genex). In total, five dietary treatments were employed in the trial. Live weight gain, feed intake, feed conversion ratio and mortality were not affected by dietary treatments throughout the experiment. However, relative weight of the small intestine of antibiotic treatment had significantly less than that of the basal diet. Intestinal microbial flora and tissue were determined at 21th and 42th days. In both periods, antibiotic or organic acids mixture treatments significantly decreased total bacteria counts. In addition to that all treatments significantly decreased gram negative bacteria counts compared to the basal diet. Probiotic treatment significantly increased ileum and jejunum villus height, whereas antibiotic treatment significantly decreased muscularis thickness compared to the basal diet.